Multifunctional Biomimetic nanoplexes for antibiotic targeted delivery against bacterial sepsis - Mr Mohammed Mohammed; Prof Calvin Omolo; Dr Usri Ibrahim; Prof Thirumala Govender (International Journal of Infectious Diseases)
Introduction: Bacterial sepsis is a life-threatening condition of significant global concern, highlighting the urgent need for innovative therapeutic strategies that exploit various disease pathways in designing advanced antibiotic delivery systems. Fucoidan (FU), a negatively charged sulfated polysaccharide from brown seaweeds, is recognized for its anti-inflammatory and antioxidant activities, making it a promising candidate for such delivery systems. By forming ionic complexes with positively charged molecules, such as antimicrobial peptides (AMPs), FU can be employed to create multifunctional antibiotic nanocarriers against sepsis. These nanosystems enhance antibacterial efficacy while simultaneously providing anti-inflammatory and antioxidant properties. Therefore, this study aimed to develop vancomycin (VCM)-loaded biomimetic nanoplexes based on a novel AMP and FU (VCM-FU-PEP-NPs), targeting bacterial sepsis's inflammatory and antioxidant pathways. Methods: The novel AMP was designed using the CellPPD online tool to achieve optimum physicochemical and biological properties and was subsequently synthesized. VCM-FU-PEP-NPs were formulated via the ionic gelation technique and characterized in terms of average particle size (PS), polydispersity index (PDI), zeta potential (ZP), entrapment efficiency (EE%), in vitro drug release, and biocompatibility. Additionally, VCM-FU-PEP-NPs were evaluated for their in vitro antibacterial, antioxidant, and anti-inflammatory activities. Results: VCM-FU-PEP-NPs had 162.6±0.2082 nm PS, 0.114±0.006 PDI, -32.6±1.190 mV ZP, and 90.92±0.82% EE%. VCM-FU-PEP-NPs were found to be biocompatible. The release profile showed that VCM-FU-PEP-NPs released 77.06±3.81% of VCM over 48 hours, compared to 100% release of bare VCM within 24 hours. VCM-FU-PEP-NPs exhibited superior antibacterial activity against both sensitive and resistant staphylococcus aureus maintained for 72 hours, compared to that of bare VCM. In addition, VCM-FU-PEP-NPs demonstrated excellent in vitro 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging ability and significantly reduced IL-6 levels in bacterial toxins-stimulated mammalian cells. Discussion: The results indicate that VCM-FU-PEP-NPs possess favorable characteristics for therapeutic applications. The nanoparticles' size, PDI, and ZP were comparable to that of previously reported FU nanoplexes by Etman SM et al, (2020), suggesting a stable formulation with good stability and dispersion properties. The high EE% ensures a significant load of VCM, which is crucial for its efficacy. The excellent biocompatibility of the nanosystem suggests a favorable biosafety profile for future use in septic patients. The sustained VCM release could prolong the VCM activity, decrease dosing frequency, and improve patient compliance. The superior antibacterial effect could be attributed to the sustained release of VCM and the synergistic effect of the AMP. This enhanced antibacterial activity underscores their potential to combat antibiotic-resistant strains more effectively than bare VCM. Additionally, the excellent DPPH radical scavenging and reduction in IL-6 levels suggest the potential antioxidant and anti-inflammatory efficacy of VCM-FU-PEP-NPs. Future work will involve in vivo evaluations in a preclinical animal model of sepsis. Conclusions: VCM-FU-PEP-NPs exhibit promising attributes as a multifunctional biomimetic nanosystem for managing bacterial sepsis.